A systematic review and meta-analysis of randomized controlled trials investigating the effects of supplementation with Nigella sativa (black seed) on blood pressure. Issue 11 (November 2016) - Sahebkar, Amirhossein; Soranna, Davide; Liu, Xiaoqiu; Thomopoulos, Costas; Simental-Mendia, Luis E.; Derosa, Giuseppe; Maffioli, Pamela; Parati, Gianfranco
Abstract : Supplemental Digital Content is available in the text Abstract : Several reports suggest a beneficial effect of Nigella sativa on cardiometabolic risk factors, including blood pressure (BP). However, the magnitude of the BP-lowering effect of N. sativa remains controversial. We aimed to calculate this effect size of N. sativa through a systematic review and meta-analysis of randomized controlled trials (RCTs). PubMed, Cochrane Collaboration Library, and SCOPUS were used as data sources of RCTs published before 30 August 2015 (in English only) comparing N. sativa treatment with placebo or standard treatment. We used random effect models to estimate the difference in BP reductions, I 2 index and χ 2 statistics to measure and test the interstudy heterogeneity. Random effect metaregression models were applied to explore the associations between BP reduction and duration of treatment, dosage of N. sativa, and type of black seed as potential confounders. Publication bias was evaluated using funnel plot and Egger's regression asymmetry test. Total 11 RCTs, including 860 hypertensive or normotensive individuals were eligible, of which 10 compared N. sativa versus placebo and one versus standard treatment. SBP and DBP means decreased from 132.85 to 125.19 mmHg and from 82.63 to 77.74 mmHg after mean treatment duration of 8.3 weeks in N. sativa groups, respectively. The difference in reductions as compared with control/standard groups were −3.26 (−5.10, −1.42; I 2 = 59%) mmHg in SBP and −2.80 (−4.28, −1.32; I 2 = 60%) mmHg in DBP. Pharmaceutical preparations of N. sativa in powder and oil demonstrated a different lowering effect (in favour of the former) on both SBP and DBP. No association was observed between SBP lowering and time on treatment, N. sativa dosage or type of N. sativa . The results of Egger's test did not indicate any publication bias. Our meta-analysis suggests that short-term treatment with N. sativa powder can significantly reduce SBP and DBP levels. More evidence is needed, however, to strengthen the available evidence and to further explore the long-term BP-lowering effect of N. sativa .